Autonomous flight algorithm of a quadcopter sensing system for methane gas concentration measurements at landfill site - Bashi, Omar Ibrahim Dallal (2018)
A landfill site is an area of land that is used to dump rubbish, either directly on the ground or by filling a hole in the ground. The landfill in such a way reduces contamination of urban and suburban areas but affects its local environment and presents an explosive and toxic risk due to the emission of harmful gases. This thesis addresses the aforementioned health and safety problems, by innovating an autonomous quadcopter drone equipped with highly accurate and efficient gas sensing hardware. This quadcopter uses an algorithm to remotely and autonomously measure the methane gas concentrations in user defined areas at landfill sites. Using this sensitive and accurate gas sensing system, it is possible to map methane gas concentrations, ascertain gas distribution and identify the hot spots for collection purposes. However, there is a perceived risk that the quadcopter can disturb the gas survey area. So, this thesis experiments to ascertain the optimal surveying patterns and sensing parameters required to accurately sense methane gas clouds with minimal selfinduced air disturbance. To survey in an unstructured landfill site environment is challenging and the quadcopter requires decisional autonomy capacities. The final algorithm proposed in this thesis, self-generates coordinates based only on the user input of three coordinate angles at the corner of the selected survey area, this makes it possible to cover an area of any dimensions. This algorithm was proposed in this thesis based on a special mathematical calculation model, which has the ability to decide the spacing between adjacent straight-line trajectories within a user defined area, this prevents the quadcopter from crashing during the survey due to reasons of overcapability. During the experimentation, accurate methane gas concentration measurements at landfill sites were obtained using the algorithm for autonomous flight, with the implementation of optimal quadcopter flight parameters and gas sensor mounting arrangements. These parameters are: the flight speed at 1m/s; the altitude at 100cm-150cm; sensing at the front of the quadcopters direction of travel; maintaining a level trajectory and sensing using a straight-line pattern. Only when the quadcopter flew with these flight parameters would the flight measurements be accurate. Also, the most suitable mounting position of the methane gas sensor was discovered to be protruding forward and affixed to the end of a tiny rod. It was ascertained that the most suitable time during working hours to measure methane concentration at a landfill site was 1pm-2pm. During the tests the weather conditions were fine and acceptable to carry out the experiments These parameters were also selected based on the practical verification experiments. Finally, the autonomous quadcopter sensing system was proved to be accurate with a sensing error of only 2.2% based on experiments carried out in this thesis work.